Clinical advances in the pharmacotherapy of congenital adrenal hyperplasia - Prete, Alessandro; Auchus, Richard J; Ross, Richard J (European journal of endocrinology, 2022)
Background Patients with 21-hydroxylase deficiency congenital adrenal hyperplasia (21OHD-CAH) have poor health outcomes with increased mortality, short stature, impaired fertility, and increased cardiovascular risk factors such as obesity. To address this, there are therapies in development that target the clinical goal of treatment, which is to control excess androgens with an adrenal replacement dose of glucocorticoid. Methods Narrative review of publications on recent clinical developments in the pharmacotherapy of congenital adrenal hyperplasia. Summary Therapies in clinical development target different levels of the hypothalamo–pituitary–adrenal axis. Two corticotrophin-releasing factor type 1 (CRF1) receptor antagonists, Crinecerfont and Tildacerfont, have been trialled in poorly controlled 21OHD-CAH patients, and both reduced ACTH and androgen biomarkers while patients were on stable glucocorticoid replacement. Improvements in glucocorticoid replacement include replacing the circadian rhythm of cortisol that has been trialled with continuous s.c. infusion of hydrocortisone and Chronocort, a delayed-release hydrocortisone formulation. Chronocort optimally controlled 21OHD-CAH in 80% of patients on an adrenal replacement dose of hydrocortisone, which was associated with patient-reported benefits including restoration of menses and pregnancies. Adrenal-targeted therapies include the steroidogenesis-blocking drug Abiraterone acetate, which reduced adrenal androgen biomarkers in poorly controlled patients. Conclusions CRF1 receptor antagonists hold promise to avoid excess glucocorticoid replacement in patients not controlled on standard or circadian glucocorticoid replacement such as Chronocort. Gene and cell therapies are the only therapeutic approaches that could potentially correct both cortisol deficiency and androgen excess.